2022
DOI: 10.1186/s12943-022-01616-7
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling in colorectal cancer: pathogenic role and therapeutic target

Abstract: Background The Wnt signaling pathway is a complex network of protein interactions that functions most commonly in embryonic development and cancer, but is also involved in normal physiological processes in adults. The canonical Wnt signaling pathway regulates cell pluripotency and determines the differentiation fate of cells during development. The canonical Wnt signaling pathway (also known as the Wnt/β-catenin signaling pathway) is a recognized driver of colon cancer and one of the most repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
202
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(203 citation statements)
references
References 272 publications
1
202
0
Order By: Relevance
“…Finally, Ade CIN TSK organoids had a significant increase of ACLY and β-catenin. These results confirm previous findings that Wnt/β-catenin pathway activation occurs during colorectal cancer development [ 38 , 39 ]; based on prior studies in human colon cancer cell lines [ 11 , 21 ], upregulation of H 2 S generation may be a potential contributing factor to this process, although the effect of H 2 S biosynthesis inhibitors has not been assessed in the current set of experiments. Interestingly, prior studies have implicated the role of the Wnt/β-catenin pathway in the upregulation of CSE in several human colon cancer cell lines [ 40 ]; whether this mechanism is operative in the current system remains to be further investigated, but there appears to be a correlation: both CSE upregulation and the induction of various Wnt/β-catenin pathway components were found to be most pronounced in the same organoids: AT, Ade CIN TS and Ade CIN TSK ( Figure 1 and Figure 3 ).…”
Section: Resultssupporting
confidence: 91%
“…Finally, Ade CIN TSK organoids had a significant increase of ACLY and β-catenin. These results confirm previous findings that Wnt/β-catenin pathway activation occurs during colorectal cancer development [ 38 , 39 ]; based on prior studies in human colon cancer cell lines [ 11 , 21 ], upregulation of H 2 S generation may be a potential contributing factor to this process, although the effect of H 2 S biosynthesis inhibitors has not been assessed in the current set of experiments. Interestingly, prior studies have implicated the role of the Wnt/β-catenin pathway in the upregulation of CSE in several human colon cancer cell lines [ 40 ]; whether this mechanism is operative in the current system remains to be further investigated, but there appears to be a correlation: both CSE upregulation and the induction of various Wnt/β-catenin pathway components were found to be most pronounced in the same organoids: AT, Ade CIN TS and Ade CIN TSK ( Figure 1 and Figure 3 ).…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have demonstrated that the PI3K/Akt and Wnt/β-catenin signaling pathways are closely associated with the occurrence and development of CRC ( 16 , 17 ). Activation of the PI3K/Akt and Wnt/β-catenin signaling pathways can promote CRC cell proliferation ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…To combat such unregulated cell growth, the influence of FOXM1 inhibitor needed to be deciphered. Firstly, an MTT assay was conducted in HCT 116 cells by treating with sequential doses of thiostrepton (5,10,15,20,25,30,40,50,60, 70, 80, 90, 100µM) for 24hrs. It was revealed that with increasing doses, the viability of HCT 116 cells kept on decreasing (Fig.…”
Section: P68-dependent Enhanced Proliferation and Migration Of Crc Ce...mentioning
confidence: 99%
“…β-catenin, an effector component of this pathway, is gaining prominence as a molecular marker of cancer. Therefore, understanding the functionality of this pathway is indispensable for developing therapies for colon cancer 5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation